2-3(x-1)=2(x-3)

Simple and best practice solution for 2-3(x-1)=2(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-3(x-1)=2(x-3) equation:


Simplifying
2 + -3(x + -1) = 2(x + -3)

Reorder the terms:
2 + -3(-1 + x) = 2(x + -3)
2 + (-1 * -3 + x * -3) = 2(x + -3)
2 + (3 + -3x) = 2(x + -3)

Combine like terms: 2 + 3 = 5
5 + -3x = 2(x + -3)

Reorder the terms:
5 + -3x = 2(-3 + x)
5 + -3x = (-3 * 2 + x * 2)
5 + -3x = (-6 + 2x)

Solving
5 + -3x = -6 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
5 + -3x + -2x = -6 + 2x + -2x

Combine like terms: -3x + -2x = -5x
5 + -5x = -6 + 2x + -2x

Combine like terms: 2x + -2x = 0
5 + -5x = -6 + 0
5 + -5x = -6

Add '-5' to each side of the equation.
5 + -5 + -5x = -6 + -5

Combine like terms: 5 + -5 = 0
0 + -5x = -6 + -5
-5x = -6 + -5

Combine like terms: -6 + -5 = -11
-5x = -11

Divide each side by '-5'.
x = 2.2

Simplifying
x = 2.2

See similar equations:

| 6.66-5.07+10.7j=-6.45+4j | | 3n+n=64 | | 72-(x-1)=-3(6w+4) | | 3d-h=5 | | 5x+4=-6+3x+18 | | =x^3-8 | | -8-5y=-12+9y | | 4x^2+4y^2+24y=52 | | 4+5x=20+4x | | 10x^2-3x-15=0 | | a^2+4a-13=-8 | | 2x^2+9x-4=7y | | 4x(x+8)=-20-2x | | 3.96+2s=1.8s | | 10x+5y=140 | | 8x+3x=-26 | | 5z+2z=180 | | 10x+3y=140 | | 4y-3x+18=0 | | y=-4(5)+20 | | 8x+10=-48 | | 5z+2z=30 | | 10sinx-x=10 | | 5+0.80*x+5.00=50.00 | | 2x+8y=76 | | 17g=16g-11 | | (x+12)=(4x-24) | | -10=2x+9 | | 0=5x^2+12x+4 | | (54-18/3)+(-6)= | | 13x-35=8x+30 | | 4sin^2=2cos+1 |

Equations solver categories